The Relationship of Cognitive Function to Nutritional Status and Blood Pressure in the Tegal Sari Mandala Village, Medan City - Nuralita, Nanda Sari; Damayanti, Amelia Eka (Universitas Muhammadiyah Sumatera Utara, 2021)
Cognitive function is an intellectual function that plays a role in carrying out daily activities. The main risk factor for impaired cognitive function is hypertension. In addition, nutritional status also influences cognitive function disorders. Currently, in Indonesia, people with increased blood pressure and unbalanced nutritional status are often found, and without realizing it can have a bad influence on cognitive function. This is a categorical analytic study with a cross-sectional method, the sampling method is non-probability sampling with consecutive sampling types, with a sample of 40 people. There is a significant difference between the difference in blood pressure on cognitive function and there is also a significant difference between nutritional status on cognitive function with a P-value = 0.001. There is a significant difference between cognitive function on blood pressure and weight gain